Assessing Needs and Planning Care in Social Work - Taylor, Brian J. (Professor of social work); Devine, Toni. (Aldershot : Arena, 1993)
Focuses on the development of the skills required at each stage of the social work process; assessment, care planning implementation and evaluation. Throughout, a balance is maintained between the focus on client involvement, and the role of the social worker in an agency.
Keywords: Social service -- Decision making; Needs assessment